The Environmental Agency's Strategy For Handling Household Waste In Bengkulu City Based On Local Regulation No. 37 Of 2019 - Riko Wijaya; Evi Lorita; Tuti Handayani IS; Bakat Seno Pratomo (Social Sciences Journal, 2026)
This study aims to identify the strategies implemented by the Environmental Agency (DLH) of Bengkulu City in managing household waste, as well as to identify the obstacles encountered during its implementation. The research employs a descriptive qualitative method with five informants, consisting of three key informants and two supporting informants, using observation, interview, and documentation techniques. The research indicators refer to Bengkulu Mayor Regulation Number 37 of 2019 concerning strategies for managing household waste and waste similar to household waste. The findings show that in terms of input, policies and human resources are considered sufficiently adequate, although facilities and infrastructure such as waste-transporting vehicles remain limited. In the process aspect, DLH has conducted socialization and coordination related to waste management. In terms of output, operational funds have been well distributed; however, challenges remain due to the limited number of waste collection vehicles. In  the outcomes aspect, the strategy has not been fully effective because public awareness regarding proper waste management and disposal is still low. Overall, DLH’s strategy has been implemented but has not yet been fully effective in addressing household waste problems in Bengkulu City.